Investigation of Laser Assisted Etching for Preparation Silicon Nanostructure and Diagnostic Physical Properties - Zahraa J. Abdulkareem; Uday M. Nayef; Kadhim A.Hubeatir (Engineering and Technology Journal, 2015)
In this paper; nanostructure porous silicon (PS) was prepared by using photo-electrochemical etching (PECE) of n-type silicon at 10 & 30 mA/cm2 etching current density for 10 minute. X-ray diffraction (XRD) confirms the formation of porous silicon and the crystal size is reduced toward nanometric scale. The Atomic Force Microscope (AFM) investigation shows the sponge like structure of PS, the width of surface pits and surface roughness increase with etching current density.Finally, the Fourier Transform Infrared (FTIR) illustrates the PS layer have large amount of dangling bonds.